2012
DOI: 10.1089/jpm.2011.0336
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Attitudes and Experiences Surrounding Palliative Sedation: Components for Developing Policy for Nursing Professionals

Abstract: Background: Nurses play an integral role in providing care for patients with end of life (EOL) symptoms refractory to conventional treatments and that may necessitate palliative sedation (PS). A paucity of research on nurses' attitudes, knowledge, and experience with PS exists, despite nurses being instrumental in evaluating its appropriateness and carrying out the care plan. Objective: The objective of the study was to elicit nurses' perspectives and conceptualizations of knowledge and skills needed to admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 22 publications
0
31
0
2
Order By: Relevance
“…This has also been seen in previous studies. 11,14,16 Morita et al 13 reported that inexperienced and younger nurses are more inclined to think about resigning because of palliative sedation. This was not reported in the current study; the nurses saw palliative sedation as an opportunity for the patient, the family, and the staff to have a dignified farewell.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This has also been seen in previous studies. 11,14,16 Morita et al 13 reported that inexperienced and younger nurses are more inclined to think about resigning because of palliative sedation. This was not reported in the current study; the nurses saw palliative sedation as an opportunity for the patient, the family, and the staff to have a dignified farewell.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Previous studies have shown that nurses believe that palliative sedation is perceived as ethically difficult and that further knowledge is required for nurses to feel secure in their role. 10,[13][14][15] Nurses have an important role in palliative sedation. The nurse is involved in the decision making, implementation, and monitoring during treatment.…”
mentioning
confidence: 99%
See 3 more Smart Citations